2020
DOI: 10.9734/ajacr/2020/v6i130151
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Water Hyacinth Powder Using FTIR Spectroscopy and the Adsorption Behaviour of Pb2+, Cd2+, Zn2+, Ni2+ and Cr2+ in Aqueous Solution

Abstract: The adsorption behavior of selected metal ions on water hyacinth powder was investigated by Fourier Transform Infrared (FTIR) spectroscopy. Water hyacinth powder was used as an adsorbent due to its popularity, low cost and ease of availability. Water hyacinth stems were dried and ground to a powder. Batch adsorption experiments were conducted at room temperature by adding known concentrations of Pb2+, Cd2+, Cr3+, Zn2+ and Ni2+ to 5 g of water hyacinth powder in different test tubes and allowed to stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…To characterize the bio composition of the plant, the following procedure has been followed [19]:  A small amount of the stems and leaves were taken to the chemical department laboratory for bio composition characterization. The small amount was rinsed with distilled water and left to dry at room temperature.…”
Section: Biodiesel Production Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize the bio composition of the plant, the following procedure has been followed [19]:  A small amount of the stems and leaves were taken to the chemical department laboratory for bio composition characterization. The small amount was rinsed with distilled water and left to dry at room temperature.…”
Section: Biodiesel Production Proceduresmentioning
confidence: 99%
“…Previous researchers discussed in this article's literature, such as [3,5,9,10,12,13,19], have also used the abovementioned standard procedures and equipment.…”
Section: Diesel and Biodiesel Characterizationmentioning
confidence: 99%
“…The strong peak at 1605.85 cm -1 and 1385.20 cm -1 were assigned to the N-H bend of primary amines and S=O stretching of sulfate. The peaks at 927.27 cm -1 and 749.04 cm -1 were assigned to O-H bend of carboxylic acids and C-Cl stretch of alkyl halides (Munene et al, 2020). From the spectra, it was observed that the intensity of the heavy metal loaded E. Crassipes was lower than the spectra of the E. Crassipes before adsorption and there was some shift or disappearance of the wave numbers after adsorption.…”
Section: Resultsmentioning
confidence: 96%
“…Water hyacinth compounds' functional groups were identified using IR spectroscopy. To create pellets with KBr, the dry powder of water hyacinth was weighed to a maximum of ± 1 mg. IR spectroscopy was then used to examine the dried pellets [13][14][15].…”
Section: Analysis Of Infrared (Ir)mentioning
confidence: 99%